GENERAL BANKING LEVEL 1 TRAINING REVIEW ON THE COMPETENCIES OF INDEPENDENT CAMPUS INTERNSHIP STUDENTS PT BANK MANDIRI (PERSERO) TBK - Lenny Menara Sari Saragih; Jifa Amanda (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Training is a process used to acquire skills, abilities and knowledge in structured ways to increase employee competency, so that training and competency are mutually sustainable. This research was conducted to review the General Banking Level 1 Training on Internship Student Competencies at the Merdeka Campus of PT Bank Mandiri (Persero) Tbk., the sample used was 58 internship students, and in collecting data the researcher used qualitative research with descriptive methods. Research is carried out by describing experiences or studies in the field more specifically (field research), data collection techniques used are questionnaires, interviews and document collection. Then, in preparing the research, the data that has been obtained is collected and implemented with a coherent and detailed explanation to find out the problem and find an explanation for the problem. PT Bank Mandiri (Persero) Tbk. is one of the state-owned banks that provides a forum with the Ministry of Education, Culture, Research & Technology for students to be able to study outside their original study program through the Independent Campus Program. The implementation of the Debriefing Training has been carried out well, judging from the results of the competency certification test, but there are still some training participants who did not pass the competency test, so it is necessary to find out again what needs to be improved.